Construção de sonda para análise de parâmetros e controle de efluentes para aterros sanitários - ITO, Roberto Kiyoshi (2020)
In world context, of discussions about the emission of landfill, global warning, and many other uncertainties that surround enviroiment, this research brings up the disussion about viable aspects of landfill automation and its cost benefits, through the survey of deposited material characteristics in landfils. To this end, this study presents a probe model capable of sending a series of information about physical phenomena occurred in landfils, especially temperature control and gas generation in grouded layers, in order to identify the maturation stage of the materials disposed in the landfill. This project is made possible by the development of new technologies that make it possible to monitor and intervene on a wide range of physical indices, wich are fundamental for the sanitary control of a landfill area. Discussing viable aspects of a landfill automation, and their cost-effectiveness, become interesting actions in the global solid waste management landscape. Using low-cost equipment consisting of a micro controller board and coupled sensors, it is possible to build this probe.. Regarding the methodology, this work is within the specific research typologies, identified as applied research, for its practical interest, since it is clear the applicability of its results in solving the problem of recovery degraded areas by the deposit of solid urban waste